Time Course of Creativity in Dance - Kirsh, David; Stevens, Catherine J.; Piepers, Daniel W. (Frontiers in Psychology, 2020)
Time-motion studies revolutionized repetitive work last century. Might time-idea studies revolutionize intellectual work this century? Collaborating with seven professional dancers we set out to discover if there were any significant patterns in when dancers come up with ideas, and when they modify or reject them. On each of three days the dancers were given a choreographic problem (or task) to help them generate a novel (high quality) contemporary dance phrase. They were videoed as they worked on this task for 15, 30 and 45 mins. At the end of each interval we had them perform the phrase they were creating. They then coded the video of themselves using a coding language we developed with them to identify when ideas are introduced, modified and rejected. We found that most ideas are created early and that though these early ideas are aggressively pruned early, many / most still make it into the final product. This supports a blended version of the ideas in design theory that creativity either devolves into iterative design – incremental improvement of a core idea – or it is the product of a succession of rapidly generated and discarded ideas – fail fast fail often. We found no evidence that one account was more predictive than the other for the domain of contemporary dance.